EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE CO-OP CO-OP, DISCOVERY LEARNING DAN PBL DENGAN PENDEKATAN SAINTIFIK SISWA KELAS VIII SMP NEGERI SE-KABUPATEN NGAWI PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KREATIVITAS BELAJAR MATEMATIKA - Kurniawan, Wahyu; Mardiyana, Mardiyana; Slamet, Isnandar (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research aims to know the effect among learning models used cooperative learning of Co-op Co-op type with scientific approach, discovery learning (DL) with scientific approach, and  the problem based learning (PBL) with scientific approach. The research method was quasi experimental. The population was all students of grade VIII State Junior High School of district Ngawi Year of 2014/2015. Sampling was taken by stratified cluster random sampling technique. The hypothesis test used two way analysis of variance with unbalanced cell. The results of the research were as follows. (1) The mathematics learning achievement of students treated with Co-op Co-op type of cooperative learning model with scientific approach was better than that of those treated with DL learning model with scientific approach and those treated with PBL learning model with scientific approach, while that of those treated with DL learning model with scientific approach was as good as that of those treated with PBL learning model with scientific approach. (2) The mathematics learning achievement of students with high learning creativity was better than that of those with medium and low ones, while that of those with medium was better than that of those with low one. (3) In Co-op Co-op type of cooperative learning model with scientific approach, the learning achievements of the students with high, medium and low learning creativities were the same. In DL learning model with scientific approach, the students with high learning creativity had mathematics learning achievement as good as those with those with medium one, while those with high and medium learning creativities had better learning achievement than those with low on. In PBL learning model with scientific approach, the students with high and low creativities had mathematics learning achievement as good as that of those with medium one, while the students with high learning creativity had better learning achievement than those with low one. (4) The students with high and medium learning creativities treated with Co-op Co-op type of cooperative learning model with scientific approach had mathematics learning achievement as good as those treated with DL with scientific approach and those treated with PBL with scientific approach. The students with low learning creativity treated with Co-op Co-op type of cooperative learning model with scientific approach had mathematics learning achievement better than those treated with DL with scientific approach, while those treated with Co-op Co-op type of cooperative learning model with scientific approach had mathematics learning achievement with scientific approach and those treated with DL with scientific approach had learning achievement as good as that of those treated with PBL with scientific approach.Keywords: Co-op Co-op, DL, PBL, scientific approach, student learning creativity